Elucidating biochemical features and biological roles of Streptomyces proteins recognizing crystalline chitin- and cellulose-types and their soluble derivatives. (7th August 2017) - Schrempf, Hildgund
Abstract: Pioneering biochemical, immunological, physiological and microscopic studies in combination with gene cloning allowed uncovering previously unknown genes encoding proteins of streptomycetes to target crystalline chitin and cellulose as well as their soluble degradation-compounds via binding protein dependent transporters. Complementary analyses provoked an understanding of novel regulators governing transcription of selected genes. These discoveries induced detecting close and distant homologues of former orphan proteins encoded by genes from different bacteria. Grounded on structure-function-relationships, several researchers identified a few of these proteins as novel members of the growing family for lytic polysaccharides monooxygenases. Exemplary, the ecological significance of the characterized proteins including their role to promote interactions among organisms is outlined and discussed. Graphical abstract: Highlights: Specific Proteins targeting crystalline chitin and cellulose, enzymes including lytic polysaccharides monooxygenases, specific transportes, ecological significance.